A novel activated-zinc antiseptic solution effective against MRSA and Pseudomonas aeruginosa: a pig model. (1st July 2022) - Hill, Derek L; Pinger, Cody; Noland, Erica L; Morton, Kevin; Hunt, Alessandra M Agostinho; Pensler, Elizabeth; Cantu, Sarah; Attar, Paul S; Siddiqi, Ahmed
Abstract : Objective: The purpose of this study was to investigate the antimicrobial efficacy of a novel activated zinc solution against meticillin-resistant Staphylococcus aureus (MRSA) and Pseudomonas aeruginosa after one hour, and to evaluate any untoward effect of the solution on local wound tissue at 24 hours after solution exposure in a pig wound model. Method: A pathogen-free, commercially raised, Yorkshire-cross female pig was acquired 12 days prior to the procedure. Within one week prior to the procedure, a small loopful of test bacteria, Pseudomonas aeruginosa (pig-isolate) and MRSA (ATCC-6538), were streaked and cultured on a non-selective agar. Full-thickness wounds (n=24) were created and evenly divided into three groups: control wounds (exposed to bacteria but untreated, n=8); wounds treated with Compound 1 (n=8), and wounds treated with Compound 2 (n=8). All wounds were dressed and monitored for one hour and 24 hours. Results: After one hour, the wounds treated with Compound 1 and Compound 2 had a mean recoverable total bacteria of 2.8 log colony forming units (CFUs) and 3.5 logCFUs, respectively. After one hour, the wounds treated with Compound 1 and Compound 2 had a mean recoverable MRSA of 2.3 logCFUs and 1.6 logCFUs, respectively (p=0.009). After one hour, the wounds treated with Compound 1 and Compound 2 had a mean recoverable Pseudomonas aeruginosa of 0.3 logCFUs and 0.0 logCFUs, respectively (p=0.000). After 24 hours of exposure to Compound 1 and Compound 2, there was no statistically significant increased necrosis (p=0.12, p=0.31, respectively) or neutrophilic infiltrate (Compound 2, p=0.12) when compared with control wounds. Conclusion: The novel activated-zinc compound used in this study demonstrated a 99.5–99.9% reduction in total bacteria, a 99.9–99.98% reduction in MRSA, and 100% eradication of Pseudomonas aeruginosa one hour after exposure. This novel solution may provide another significant tool to treat and/or prevent wound infections.